Quick Exit or Deliberate Loosening? On the Future of Contact Restrictions in the COVID-19Crisis - Sebastian Dullien; Alexander Herzog-Stein; Peter Hohlfeld; Sven Schreiber; Silke Tober (Wirtschaftsdienst)
Abstract How important is the relaxation of contact restrictions for the recovery of the German economy and what conclusions can be drawn for the appropriate level of contact restrictions in the coming months? In considering these issues, an attempt will be made to assess what significance the contact restriction measures introduced by the federal and state governments since mid-March 2020 will actually have for the current slump in economic activity in Germany. In addition, the various plausible scenarios for the spread and containment of infection are presented with different options for easing contact restrictions.